Avaliação do efeito da progesterona sintética em macrófitas (Salvinia auriculata) - Sant’ana, Laiane Neri (Universidade Federal de São Carlos, 2023)
Microcontaminants are substances that have been found in various environmental compartments. These compounds raise concerns about their effects in the medium to long term, especially the category of endocrine disruptors that can cause damage to biodiversity such as a drop in fertility and genetic changes in living beings. In this context, this study evaluated the action of synthetic progesterone on the growth of the leaf area of the floating macrophyte Salvinia auriculata. Considering that it is a microcontaminant drug, it is believed that progesterone causes negative impacts on the development (growth and reproduction) of S. auriculata. Three different concentrations of progesterone diluted in water were analyzed: Treatment A = 0.225 mg/L, B = 0.450 mg/L and C = 0.900 mg/L. For each concentration, 100 individuals of S. auriculata were used, 50 for the Control Treatment (without hormone addition) and 50 for the other treatments. The leaf area of S. auriculata, in each treatment, was measured over 5 weeks and, subsequently, mathematical modeling was used to parameterize the growth of the macrophyte. Surprisingly, the results showed that the growth of S. auriculata was significantly more accelerated in treatments with progesterone, suggesting that this hormone stimulated its growth at the tested concentrations. However, the high growth of macrophytes can also be harmful to aquatic environments, making the multiple uses of water difficult and reducing the productivity of submerged plants, since floating species, such as S. auriculata, block sub-aquatic radiation.
Evaluation of the effect of synthetic progesterone on macrophytes (Salvinia auriculata)
Keywords: Contaminantes emergentes; Disruptores endócrinos; Modelos matemáticos; Emerging contaminants; Endocrine disruptors; Mathematical modeling; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS